Investigation of the Effects of Human Resource Management (HRM) practices on Corporate Social Responsibility (CSR), A Study in Zabol University of Medical Sciences - Mohammad Mostafa Dahmardeh (Journal of Global Pharma Technology, 2017)
The purpose of the present study is to investigate the effects of human resources management (HRM) practices on corporate social responsibility in Zabol University of Medical Sciences. The independent variable in this study is the practices of human resources management. Human resources management focuses on policies, procedures and systems that affect the behaviour, thoughts and actions of employees. Dependent variable of this study is the organizational performance. The organizational performance is defined as the manner of performing tasks and activities and the results of them. The social responsibility is the mediator variable of this study. Social responsibility is defined as tasks and obligations that the organization must do to protect and help the society in which it works. The hypotheses of this research are based on the impact of the independent variable on the dependent variable with respect to the role of mediator variable. The statistical population of this study is the headquarters of Zabol University of Medical Sciences. The minimum sample size according to Cochran’s formula is estimated to be 102 people that have been selected by simple random sampling. The findings of this study have approved all primary and secondary hypotheses of research and show that the human resources management practices has a significant impact on the organizational performance through social responsibility.Keywords: Human resources management (HRM) practices, Corporate social responsibility (CSR), Organizational performance